Open Government and Electronic Government for Localising the Sustainable Development Goals: A Qualitative Case Study of the Jakarta Provincial Government, Indonesia - Muh Kadarisman; Izzatusholekha Izzatusholekha; Dwiky Lucky Adiyasha (Universitas Muhammadiyah Jakarta, 2025)
This article examines how open government and electronic government support the localisation of the Sustainable Development Goals (SDGs) in the Jakarta Provincial Government, Indonesia. Although digital platforms have become central to contemporary public administration, their contribution to sustainable development depends not only on technological availability but also on institutional coordination, data quality, public participation, and accountability. Using a descriptive qualitative case-study design, the article analyses documentary materials, policy instruments, and interview-based evidence from thirteen purposively selected informants representing provincial government units. The study is grounded in the uploaded Indonesian research material on open government and electronic government in the SDGs framework in Jakarta and is strengthened by recent international and Indonesian policy literature on open data, e-governance, and SDG implementation. The findings indicate that Jakarta has institutionalised important elements of open government through Jakarta Open Data, Satu Data Jakarta, smart-city initiatives, and web-based public information services. These platforms increase the visibility of government datasets, strengthen the possibility of evidence-based planning, and create channels through which citizens, researchers, businesses, and civil society organisations can monitor public programmes. However, the impact of these initiatives remains uneven. The main constraints include inconsistent updating of datasets, limited interoperability across agencies, insufficient digital literacy among segments of society, uneven monitoring and evaluation, cybersecurity concerns, and the risk that transparency becomes procedural rather than deliberative. The article argues that open government and electronic government can function as enabling infrastructures for SDG 9, SDG 11, SDG 16, and SDG 17 when they are integrated with participatory planning, high-quality metadata, privacy protection, service co-design, and measurable institutional accountability.